Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1055/s-0037-1608621
|View full text |Cite
|
Sign up to set email alerts
|

Use of Incisional Negative Pressure Wound Therapy in Skin-Containing Free Tissue Transfer

Abstract: NPWT may be employed in a fashion similar to the standard incisional application. With this technique, serial flap examination remains possible and is not associated with pedicle compression or increased rates of flap loss. Interestingly, no splints were utilized with the VAC device which itself may serve as a relative immobilizer of an extremity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 35 publications
0
37
0
Order By: Relevance
“…Korber et al conducted a study on the postoperative use of VAC on a mesh graft in patients with chronic ulcers and found that the healing rate was significantly higher in the VAC treatment group compared with the conventional dressing group [9]. Similarly, studies have also reported that a VAC dressing without a splint can effectively produce a uniform compressive force and firmly fix the graft in place compared with the conventional bolster dressing [16,17]. Waltzman et al carried out a large sample study to reveal that split-thickness skin grafts (SFSGs) can be well-secured with VAC, especially in patients with burn injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Korber et al conducted a study on the postoperative use of VAC on a mesh graft in patients with chronic ulcers and found that the healing rate was significantly higher in the VAC treatment group compared with the conventional dressing group [9]. Similarly, studies have also reported that a VAC dressing without a splint can effectively produce a uniform compressive force and firmly fix the graft in place compared with the conventional bolster dressing [16,17]. Waltzman et al carried out a large sample study to reveal that split-thickness skin grafts (SFSGs) can be well-secured with VAC, especially in patients with burn injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Characteristics of included studies are included in ►Table 1. [11][12][13][14][15][16][17][18][19][20] These studies fulfilled our inclusion and exclusion criteria after analysis of the full content of the articles. Results of quality analysis of each study are illustrated in ►Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Chim et al and Bi et al have also demonstrated that negative pressure therapy can be used reliably in free tissue transfer. 4,5 Indeed, we have additionally utilized NPWT around fasciocutaneous flaps in situations where trauma has precluded primary closure due to swelling. However, the limitations to the above mentioned studies were their small sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…There were no complications related to the use of negative pressure therapy and no flap losses, which once again demonstrates that use of negative pressure immediately postoperatively does not increase flap loss or compromise the pedicle supplying the flap. 5 Eisenhardt and associates examined 26 patients with NPWT lower extremity soft tissue defects observing just two flap failures both occurring in patients with comorbid peripheral vascular disease. 6 In our retrospective, multi-institutional study performed over 9 years, we were able to review 97 cases of negative pressure therapy utilized immediately over split-thickness skin grafted free muscle flaps.…”
mentioning
confidence: 99%